Myocarditis and pericarditis in individuals exposed to the Ad26.COV2.S, BNT162b2 mRNA, or mRNA-1273 SARS-CoV-2 vaccines - Pareek, Manan; Sessa, Pasquale; Polverino, Paolo; Sessa, Francesco; Kragholm, Kristian Hay; Sessa, Maurizio (Frontiers in Cardiovascular Medicine, 2023)
What are the current reporting rates of myocarditis and pericarditis in the US for COVID-19 vaccines, and are these adverse events disproportionally reported among the different COVID-19 vaccines?Findings: In this study, we found reporting rates of myocarditis and pericarditis after COVID-19 vaccination to be less than 0.1%. Rates were highest for the BNT162b2 mRNA vaccine, followed by the mRNA-1273 and Ad26.COV2.S vaccines, respectively.The results of this study suggest that the reporting rates of cardiovascular complications such as myocarditis and pericarditis secondary to vaccination remain less common than the rates seen for active SARS-CoV-2 infection.